Bantuan Rehabilitasi Rumah bagi Warga Miskin di Kota Padang - Achmadi Jayaputra (Jurnal Penelitian Kesejahteraan Sosial, 2013)
The Ministry of Social Affairs holds a Social Rehabilitation Program for the citizens having unadequate home condition for living. The program aimed at the poors by providing assistance in the form of funds Rp 10.000.000,- per family to rehabililate their homes. The goal of the program is that the poors can improve their own homes in order to meet the health requirements. The implementation of the program activities is to go through the process set out by the guidelines to be followed in some stages. Research locations is chosen purposively in Lubuk Buayo District, Padang. At this location, assistance has been provided to 50 families. Data sources are obtained from the informations of several informants encountered. The research result shows that there are some poor people who can perform these activities in accordance to the stages guided, while some are not able to complete the renovation of the houses. Therefore, the model suggested that home assistance repairement should be provided and based on the situation and condition of the poors participating in the program.